Introducing Autodesk 3ds max 2011 : Autodesk official training guide - Derakhshani, Randi; Derakhshani, Dariush (Serious skills., 2010)
An Autodesk Official Training Guide to 3ds Max 2011 3ds Max is a popular 3D animation-and-effects software used in movies, visual effects, games, cartoons, short films, commercials, and other animation. However, it also presents a number of challenges to newcomers. This introduction to the latest version breaks down the complexities of learning 3D software and walks you through the basics of modeling, texturing, animating, and using visual effects. Real-world examples from talented beginning 3ds max users motivate you to learn the software and helpful tutorials offer realistic, professional challenges for you to unravel. In addition, each chapter is richly illustrated with workflows to make learning 3ds max 2011 much easier and fn. Introduces you to the basics of modeling, texturing, animating, and incorporating visual effects using the latest version of 3ds Max software Features excellent tutorials, helpful examples, detailed workflows, and a companion Web site to enhance your learning experience Explains a variety of methods for solving real-world challenges and breaks down why certain methods are used Makes the transition of coming from other 3D software applications as smooth as possible Introducing 3ds Max 2011 takes a typically difficult subject and breaks into easily digestible pieces so you can confidently begin working with this 3D animation software today.